The Economics of Higher Education in Nepal: Developing a Sustainability Plan - Sanjaya Acharya (Journal of Education and Vocational Research, 2021)
Nepal universities are in a delicate transition now. The enrolment of students is not encouraging; rather it is declining over the years particularly in public universities. Consequently, the outflow of Nepalese students has got momentum over two decades; and nearly a half-million Nepalese students are currently enrolled in foreign universities. The quality education in Nepalese universities is crucial for the return as well as the significant inflow of Nepalese students in the universities of their homeland. However, higher education requires a sustainability plan particularly for the resource generation and promotion of scientific research/publications. Long-term vision, mission, and strategic measures are particularly lacking in Nepal universities. This requires setting objectives and attainable milestones along with specific strategic measures and financial planning that are missing now. The contribution of this paper is twofold. First, it proposes a monitoring framework in the form of a regression model to use as a tool and observe the improvement in higher education in the country. Secondly, it has proposed a typical Sustainability Plan considered appropriate to Nepal; however, it might be equally replicable to other universities of the developing world. Moreover, it has also suggested measures to make such a plan a success.